Rising above the gathering storm : energizing and employing America for a brighter economic future (National Academies Press, 2007)
"Today, the United States leads the world in science and technology development and enjoys a robust economy derived in large part from scientific and technological innovation. However, there are danger signs that US advantages in the marketplace and in science and technology are being threatened. Rising Above the Gathering Storm, a report from the National Academies, sounds a strong warning that the United States is losing its global competitive edge in science and technology and that US prosperity will decline unless we take concrete steps now." "This congressionally requested report makes 4 recommendations along with 20 implementation actions that federal policymakers should take to create high-quality jobs and focus new science and technology efforts on meeting the nation's needs, especially in the area of clean, affordable energy."--Jacket